2020
DOI: 10.1038/s41598-020-66497-6
|View full text |Cite
|
Sign up to set email alerts
|

α-synuclein overexpression in the retina leads to vision impairment and degeneration of dopaminergic amacrine cells

Abstract: the presence of α-synuclein aggregates in the retina of parkinson's disease patients has been associated with vision impairment. In this study we sought to determine the effects of α-synuclein overexpression on the survival and function of dopaminergic amacrine cells (DACs) in the retina. Adult mice were intravitreally injected with an adeno-associated viral (AAV) vector to overexpress human wild-type α-synuclein in the inner retina. Before and after systemic injections of levodopa (L-DOPA), retinal responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
6
36
1
Order By: Relevance
“…Indeed, quantification of the SSVEP (Afsari et al, 2014;Petridi et al, 2020) revealed altered synaptic efficacy caused by α-syn accumulation in TH>WT-α-syn-EGFP flies. These observations in Drosophila are in line with a recent study in rodents which showed that overexpression of α-syn caused impairment in the electroretinogram and loss of TH positive amacrine cells in the retina (Marrocco et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, quantification of the SSVEP (Afsari et al, 2014;Petridi et al, 2020) revealed altered synaptic efficacy caused by α-syn accumulation in TH>WT-α-syn-EGFP flies. These observations in Drosophila are in line with a recent study in rodents which showed that overexpression of α-syn caused impairment in the electroretinogram and loss of TH positive amacrine cells in the retina (Marrocco et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…As for (Thy-1)-hu-A30P-α-Syn transgenic mice and PD patients' retinas, pSer129α-Syn accumulation were found in cells bodies of GCL and INL, and in the IPL neurites ( Figure 3A). These results were mirrored by an early loss in the number of TH + amacrine cells (Figures 3B,C) that precede in time the loss of the RGCs (Marrocco et al, 2020). Notably this study demonstrated for the first time that α-Syn overexpression in the retina leads to neurodegeneration of DA amacrine cells, causing retinal-specific defects and consequent visual impairment that resemble the human PD phenotype (Marrocco et al, 2020).…”
Section: Visual and Retinal Abnormalities In Pd Animal Modelssupporting
confidence: 53%
“…These results were mirrored by an early loss in the number of TH + amacrine cells (Figures 3B,C) that precede in time the loss of the RGCs (Marrocco et al, 2020). Notably this study demonstrated for the first time that α-Syn overexpression in the retina leads to neurodegeneration of DA amacrine cells, causing retinal-specific defects and consequent visual impairment that resemble the human PD phenotype (Marrocco et al, 2020). These findings is even more interesting in light of very recent evidence reporting a specific reduction of the DAC number as well as of the number of their synaptic contacts with AII amacrine cells and melanopsin cells reported in the retina of PD patients (Ortuno-Lizaran et al, 2020).…”
Section: Visual and Retinal Abnormalities In Pd Animal Modelsmentioning
confidence: 78%
See 2 more Smart Citations